Marvel-verse. Venom. - Yamtov, Nelson; Michelinie, David; Van Lente, Fred; Tamaki, Mariko (Marvel Worldwide, Inc, 2020)
A collection of Marvel comic books featuring the origin story of the Spider-Man villain, Venom--it all begins when Peter Parker bonds with a symbiote from space to create his symbiotic black costume, only to realize the symbiote has a terrible affect on his mind. Spidey scorns the suit and symbiote, but when he casts it off the symbiote finds angry, disgraced reporter Eddie Brock, and together the two become Venom.